Analysis of the intercaste transcriptional profile of Melipona scutellaris latreille, 1811 (hymenoptera, apidae, meliponini) by mRNA differential display - Siquieroli, Ana Carolina Silva; Vieira, Carlos Ueira; Carvalho-Zelse, Gislene A.; Goulart, L. R.; Kerr, Warwick Estevam; Bonetti, Ana Maria (Biological Research, 2009)
In colonies of Melipona scutellaris Latreille, 1811 workers can be found with four ganglion nerve cells, a morphological characteristic of the queen. It is hypothesized that these workers, called intercastes, or phenocopies, are phenotypically-like workers, but genotypically identical to queens due to this specific trait. Workers with the same number of ganglion as queens seem to be intercastes between queens and workers. Our objective was to analyze the mRNA profiles of workers, queens, and intercastes of M. scutellaris through DDRT-PCR. Three hundred (300) pupae with white eyes were collected and externally identified according to the number of abdominal nerve ganglions: workers (5 ganglions), queens (4 ganglions) and intercastes (4 ganglions). The analysis identified differentially expressed transcripts that were present only in workers, but absent in intercastes and queens, confirming the hypothesis, by demonstrating the environmental effect on the queen genotype that generated phenotype-like workers.
Keywords: Rna, Messenger; Abdominal Ganglion; Cell Count; Controlled Study; Gene Expression Profiling; Genetic Transcription; Genetic Variability; Insect Caste; Melipona Scutellaris; Nonhuman; Pupa (life Cycle Stage); Queen (insect); Reverse Transcription Polymerase Chain Reaction; Rna Analysis; Species Comparison; Stingless Bee; Worker (insect); Apidae; Hymenoptera; Melipona; Melipona Scutellaris; Meliponinae; Zosteropidae